Perlindungan Hukum Kreditur terhadap Obyek Fidusia akibat Perjanjian Kredit Sebelumnya - Wihandriati Wihandriati (Faculty of Law Universitas Muhamadiyah Yogyakarta, 2022)
The binding of fiduciary guarantees is expected to provide legal certainty for creditors in carrying out the execution of collateral objects if the debtor defaults. Legal certainty can arise as a result of fiduciary guarantee objects that are registered and have executive power. The problem that often occurs is that the object of fiduciary guarantees has not been removed from fiduciary guarantees after the debtor has paid off his debt on the previous credit binding guarantee. As a result, the object cannot be created as a fiduciary guarantee if a new creditor re-registers the fiduciary guarantee. The purpose of conducting this research is to find out how the legal protection for creditors for fiduciary objects has not been removed from fiduciary guarantee objects in previous credit agreements. In this research, it is normative legal research using data analysis techniques, namely qualitative analysis techniques. The analysis technique uses legal material that is considered relevant to the problem, and is followed by analysis and presentation in descriptive writing. The results of this study are that there are two kinds of legal protection that can be provided, namely preventive legal protection and repressive legal protection.